Seawater carbonate chemistry and bioerosion of croal reef - Prouty, Nancy G; Cohen, Anne L; Yates, Kimberly Kaye; Storlazzi, Curt D; Swarzenski, Peter W; White, Lisa D (PANGAEA, 2017)
Ocean acidification (OA), the gradual decline in ocean pH and [CO3 ] 2- caused by rising levels of atmospheric CO2, poses a significant threat to coral reef ecosystems, depressing rates of calcium carbonate (CaCO3) production, and enhancing rates of bioerosion and dissolution. As ocean pH and [CO3] 2- decline globally, there is increasing emphasis on managing local stressors that can exacerbate the vulnerability of coral reefs to the effects of OA. We show that sustained, nutrient rich, lower pH submarine groundwater discharging onto nearshore coral reefs off west Maui lowers the pH of seawater and exposes corals to nitrate concentrations 50 times higher than ambient. Rates of coral calcification are substantially decreased, and rates of bioerosion are orders of magnitude higher than those observed in coral cores collected in the Pacific under equivalent low pH conditions but living in oligotrophic waters. Heavier coral nitrogen isotope (delta15N) values pinpoint not only site-specific eutrophication, but also a sewage nitrogen source enriched in 15N. Our results show that eutrophication of reef seawater by land-based sources of pollution can magnify the effects of OA through nutrient driven-bioerosion. These conditions could contribute to the collapse of coastal coral reef ecosystems sooner than current projections predict based only on ocean acidification.
Keywords: Benthos; Calcification/Dissolution; Coast and continental shelf; Entire community; Field observation; Growth/Morphology; Rocky-shore community; South Pacific; Tropical